Step
*
1
1
1
2
2
1
of Lemma
satisfies-negate-poly-constraint
1. eqs : iPolynomial() List
2. ineqs : iPolynomial() List
3. f : ℤ ⟶ ℤ
4. ¬(∀p∈eqs.int_term_value(f;ipolynomial-term(p)) = 0 ∈ ℤ)
5. ¬((∀p∈eqs.int_term_value(f;ipolynomial-term(p)) = 0 ∈ ℤ) ∧ (∀p∈ineqs.0 ≤ int_term_value(f;ipolynomial-term(p))))
⊢ (∃e∈eqs. (0 ≤ int_term_value(f;ipolynomial-term(minus-poly(add-ipoly(e;const-poly(1))))))
∨ (0 ≤ int_term_value(f;ipolynomial-term(add-ipoly(e;const-poly(-1))))))
∨ (∃ineq∈ineqs. 0 ≤ int_term_value(f;ipolynomial-term(minus-poly(add-ipoly(ineq;const-poly(1))))))
BY
{ (OrLeft THENA Auto) }
1
1. eqs : iPolynomial() List
2. ineqs : iPolynomial() List
3. f : ℤ ⟶ ℤ
4. ¬(∀p∈eqs.int_term_value(f;ipolynomial-term(p)) = 0 ∈ ℤ)
5. ¬((∀p∈eqs.int_term_value(f;ipolynomial-term(p)) = 0 ∈ ℤ) ∧ (∀p∈ineqs.0 ≤ int_term_value(f;ipolynomial-term(p))))
⊢ (∃e∈eqs. (0 ≤ int_term_value(f;ipolynomial-term(minus-poly(add-ipoly(e;const-poly(1))))))
∨ (0 ≤ int_term_value(f;ipolynomial-term(add-ipoly(e;const-poly(-1))))))
Latex:
Latex:
1.  eqs  :  iPolynomial()  List
2.  ineqs  :  iPolynomial()  List
3.  f  :  \mBbbZ{}  {}\mrightarrow{}  \mBbbZ{}
4.  \mneg{}(\mforall{}p\mmember{}eqs.int\_term\_value(f;ipolynomial-term(p))  =  0)
5.  \mneg{}((\mforall{}p\mmember{}eqs.int\_term\_value(f;ipolynomial-term(p))  =  0)
\mwedge{}  (\mforall{}p\mmember{}ineqs.0  \mleq{}  int\_term\_value(f;ipolynomial-term(p))))
\mvdash{}  (\mexists{}e\mmember{}eqs.  (0  \mleq{}  int\_term\_value(f;ipolynomial-term(minus-poly(add-ipoly(e;const-poly(1))))))
\mvee{}  (0  \mleq{}  int\_term\_value(f;ipolynomial-term(add-ipoly(e;const-poly(-1))))))
\mvee{}  (\mexists{}ineq\mmember{}ineqs.  0  \mleq{}  int\_term\_value(f;ipolynomial-term(minus-poly(add-ipoly(ineq;const-poly(1))))))
By
Latex:
(OrLeft  THENA  Auto)
Home
Index